Essential maths for engineering and construction : how to avoid mistakes - Breach, M. (Mark) (Milton Park, Abingdon, Oxon : Spon Press, 2011)
'Don't let your mathematical skills fail you! We all make mistakes; who doesn't? But they can be avoided when you understand why you make them. In engineering, construction and science exams, marks are often lost through carelessness or from not fully understanding the maths involved. When there are only a few marks on offer for a part of a question there may be full marks for a right answer and none for a wrong one, regardless of the thought that went into answering. Taking mistakes that undergraduate students often make as a starting point, this book not only looks at how you can prevent mistakes but provides an introduction to the core mathematical skills required for your degree discipline. The book contains many practice questions and fully worked answers, so whether you struggle with algebra, geometry, statistics, calculus or any of the other mathematical areas vital to your degree, this book will guide you around the pitfalls. Focusing on the recognition, correction and avoidance of common errors to improve the clarity of your maths work and mathematical understanding, this book is for any undergraduate who does mathematics - and sometimes makes mistakes'--
Keywords: Mathematics -- Textbooks